Extensive Variations in Diurnal Growth Patterns and Metabolism Among Ulva spp. Strains. Issue 1 (12th February 2019) - Fort, Antoine; Lebrault, Morgane; Allaire, Margot; Esteves-Ferreira, Alberto A.; McHale, Marcus; Lopez, Francesca; Fariñas-Franco, Jose M.; Alseekh, Saleh; Fernie, Alisdair R.; Sulpice, Ronan
Abstract : Sea lettuce (Ulva spp.) strains show extensive variation in growth and metabolism, demonstrating a large potential for strain selection in boosting biomass and metabolite yields in aquaculture. Abstract: Green macroalgae of the genus Ulva play a key role in coastal ecosystems and are of increasing commercial importance. However, physiological differences between strains and species have yet to be described in detail. Furthermore, the strains of Ulva used in aquaculture usually originate from opportunistic collection in the wild without prior selection of best performing strains. Hence, efforts are required to detect the potential variability in growth and metabolic accumulation between Ulva strains and ultimately select the best performing strains under given environmental conditions. Here, the growth, physiological, and metabolic characteristics of 49 laminar Ulva spp. strains were investigated using a custom-made high-throughput phenotyping platform, enzymatic assays, and gas chromatography-mass spectrometry. We found large natural variation for a wide range of growth and metabolic characteristics, with growth rates varying from 0.09 to 0.37 mg.mg −1 .d −1 among strains. Ulva spp. possess a unique diurnal growth pattern and primary metabolism compared with land plants, with higher growth rates during the night than during the light period. Starch and sucrose only contributed on average 35% of the carbon required to sustain Ulva 's night growth. Nitrates accumulated during the night in Ulva tissues, and nitrate accumulation and consumption was positively correlated with growth. In addition, we identified six amino acids as possible biomarkers for high growth in Ulva . The large variability in growth and metabolite accumulation recorded among morphologically similar Ulva strains justifies future efforts in strain selection for increasing biomass, metabolite yields, and nutrient removal in the growing aquaculture industry.